Experimentally‐induced anti‐myeloperoxidase vasculitis does not require properdin, MASP‐2 or bone marrow‐derived C5. Issue 1 (September 2016) - Freeley, Simon J; Popat, Reena J; Parmar, Kiran; Kolev, Martin; Hunt, Beverley J; Stover, Cordula M; Schwaeble, Willhelm; Kemper, Claudia; Robson, Michael G
Abstract: Anti‐neutrophil cytoplasmic antibody vasculitis is a systemic autoimmune disease with glomerulonephritis and pulmonary haemorrhage as major clinical manifestations. The name reflects the presence of autoantibodies to myeloperoxidase and proteinase‐3, which bind to both neutrophils and monocytes. Evidence of the pathogenicity of these autoantibodies is provided by the observation that injection of anti‐myeloperoxidase antibodies into mice causes a pauci‐immune focal segmental necrotizing glomerulonephritis which is histologically similar to the changes seen on renal biopsy in patients. Previous studies in this model have implicated the alternative pathway of complement activation and the anaphylatoxin C5a. Despite this progress, the factors that initiate complement activation have not been defined. In addition, the relative importance of bone marrow‐derived and circulating C5 is not known. This is of interest given the recently identified roles for complement within leukocytes. We induced anti‐myeloperoxidase vasculitis in mice and confirmed a role for complement activation by demonstrating protection in C3‐deficient mice. We showed that neither MASP‐2‐ nor properdin‐deficient mice were protected, suggesting that alternative pathway activation does not require properdin or the lectin pathway. We induced disease in bone marrow chimaeric mice and found that circulating and not bone marrow‐derived C5 was required for disease. We have therefore excluded properdin and the lectin pathway as initiators of complement activation and this means that future work should be directed at other potential factors within diseased tissue. In addition, in view of our finding that circulating and not bone marrow‐derived C5 mediates disease, therapies that decrease hepatic C5 secretion may be considered as an alternative to those that target C5 and C5a. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.